MODERN EDUCATIONAL TECHNOLOGIES: TEACHING METHOD, PEDAGOGICAL METHODOLOGY, PEDAGOGICAL PROCESS - Sharipova Fotima Kakhramonovna (International Journal on Integrated Education, 2023)
The article describes the importance of modern educational technologies and measures for their development, and also discusses the concepts of educational technology, teaching method, form of teaching and pedagogical methodology. The stages of teaching methods and forms of teaching in the classroom and the matrix diagram are explained.